Pengaruh Kualitas Layanan Yang Dirasakan Terhadap Niat Perilaku Wisatawan Dengan Kepuasan Sebagai Variabel Mediasi: (Studi Pada Wisata Bukit Kehi, Pamekasan) - Hoirul Anam; AS , Fathor (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the effect of perceived service quality on tourists' behavioral intention with satisfaction as a mediating variable at Bukit Kehi, Pamekasan. A quantitative method using questionnaires and SmartPLS 4 was employed. The results show that service quality significantly affects tourist satisfaction but has no direct effect on behavioral intention. Satisfaction significantly influences behavioral intention and mediates the relationship between service quality and intention. These findings suggest that enhancing service quality can indirectly increase tourists' intention to revisit through improved satisfaction.